2021
DOI: 10.1002/smll.202006687
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ Coupling Strategy toward Porous Carbon Liquid with Permanent Porosity

Abstract: An in situ coupling approach is used to fabricate the porous carbon liquid with permanent porosity by directly dispersing hollow carbon nanospheres in polymerized ionic liquids. It is a kind of homogenous and stable type III porous liquid at room temperature. Because of the well‐preserved permanent porosity, this unique porous carbon liquid is capable of absorbing the largest quantity of carbon dioxide than the reference PILs and solid carbon liquid, thus, can function as a promising candidate for application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…27 Subsequently, CO 2 absorption isotherms have been measured in many porous liquids when the system consists of only components with little to no vapor pressure. 31,34,35,37,40,42,43,45,46,48,49,51,52 Gravimetric absorption of CO 2 and CH 4 has also been measured in type III porous liquids, 41 as well as water vapor sorption for surface modified surface modified UiO-66 based porous liquids. 48 The latter, water vapor sorption, is an interesting method in that it can theoretically quantify the pore volume of certain porous liquid systems ( i.e.…”
Section: Characterisation Of Porous Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Subsequently, CO 2 absorption isotherms have been measured in many porous liquids when the system consists of only components with little to no vapor pressure. 31,34,35,37,40,42,43,45,46,48,49,51,52 Gravimetric absorption of CO 2 and CH 4 has also been measured in type III porous liquids, 41 as well as water vapor sorption for surface modified surface modified UiO-66 based porous liquids. 48 The latter, water vapor sorption, is an interesting method in that it can theoretically quantify the pore volume of certain porous liquid systems ( i.e.…”
Section: Characterisation Of Porous Liquidsmentioning
confidence: 99%
“…For example, in 2019 Li and coworkers reported that colloidally stable type III porous liquid dispersions could be formed in poly(dimethylsiloxane) (PDMS) by surface modifying UiO-66 particles using a controlled radical polymerisation technique, 48 and in 2020 James and co-workers vastly expanded this family of porous liquids by screening a broad range of porous materials (including MOFs, zeolites, and a porous organic polymer) in a variety of non-ionic liquids (including oils and polyethylene glycols). 49 While most of these systems relied on the use of a MOF, ZIF, or zeolite, as the porous material, more recently there have been examples of alternative pore carriers being used to form type III porous liquids, including the dispersion of HS nanospheres in dimethylaminoethoxyethanol, 50 hollow carbon nanospheres in polymeric ionic liquids, 51 and POC microparticles in a range of oils and ionic liquids. 52 The utilisation of ionic liquids in the formation of porous liquids has several advantages, not least the negligible vapor pressure of most systems, and recently ionic liquids were also incorporated into type I and type II systems.…”
Section: Key Milestones In the Development Of Porous Liquidsmentioning
confidence: 99%
“…The in situ coupling strategy can produce PLs using varied structures such as porous carbon nitride, porous boron nitride, and polymers with intrinsic microporosity. 114 Recently, a novel type III PL based on COF was made. The outer shell of COF was functionalized to improve the dispersion stability of COF suspension in acetonitrile.…”
Section: Types Of Porous Iquidsmentioning
confidence: 99%
“…This is also a widely used effective method in an army of other previous studies. [32][33][34] However, the above-mentioned synthesis process of PLs involved complex organic synthesis, and some synthesis required dialysis or evaporation, which significantly limited the possibility of practical implementation. Adoption of feasible and simple preparation methods to construct MOF PLs has not been reported thus far.…”
Section: Introductionmentioning
confidence: 99%